If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + i)(2 + 2i) = 0 Multiply (3 + i) * (2 + 2i) (3(2 + 2i) + i(2 + 2i)) = 0 ((2 * 3 + 2i * 3) + i(2 + 2i)) = 0 ((6 + 6i) + i(2 + 2i)) = 0 (6 + 6i + (2 * i + 2i * i)) = 0 (6 + 6i + (2i + 2i2)) = 0 Combine like terms: 6i + 2i = 8i (6 + 8i + 2i2) = 0 Solving 6 + 8i + 2i2 = 0 Solving for variable 'i'. Factor out the Greatest Common Factor (GCF), '2'. 2(3 + 4i + i2) = 0 Factor a trinomial. 2((3 + i)(1 + i)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(3 + i)' equal to zero and attempt to solve: Simplifying 3 + i = 0 Solving 3 + i = 0 Move all terms containing i to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + i = 0 + -3 Combine like terms: 3 + -3 = 0 0 + i = 0 + -3 i = 0 + -3 Combine like terms: 0 + -3 = -3 i = -3 Simplifying i = -3Subproblem 2
Set the factor '(1 + i)' equal to zero and attempt to solve: Simplifying 1 + i = 0 Solving 1 + i = 0 Move all terms containing i to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + i = 0 + -1 Combine like terms: 1 + -1 = 0 0 + i = 0 + -1 i = 0 + -1 Combine like terms: 0 + -1 = -1 i = -1 Simplifying i = -1Solution
i = {-3, -1}
| (3x/4)+2=4x-1 | | 10x+80+4x=360 | | 3x(4x-10)=-126 | | 2(3w)+2w=80 | | 5(r-3)=2n-6 | | v=Ih | | 6/11=c/77 | | t+23.7=80.66 | | 8(x+8)=7x-42+x | | -5(5y-9)-y=-3(y-3) | | 8(x+8)=7z-42+z | | 12x^2-7x-4=0FActor | | 6x+5=21/x | | 1.5*2.25= | | 8=5-3x | | 2n-12=9n-63 | | 1+2x=2(2x+2)-3(1x-4) | | 12x^2-7x-4=0 | | 2.5*2.25= | | 15/3*2+3-4-3-7 | | (9-3i)-(2+i)= | | -6(7y-2)=31+9y | | 1+2x=2(x+2)-3(1x-4) | | -6=3t-36 | | 4t(6*6)/78t=567 | | 8n+32=2n-8 | | 4t(6*6)/78t= | | -25/24=-2/3-3/2n | | -310=5(7a-6) | | 31+8v=-1+7(3v-1) | | 11-(x/4)=-23 | | 9/4=f/28 |